Phenotypic plasticity of the cyanobacterium Rhabdoderma lineare (Chroococcales, Synechococcaceae) associated with the rhodophyte Porphyridium purpureum (Porphyridiales, Porphyridiaceae) in a wetland planktonic community, new records for Peru - Montoya T., Haydee; Museo de Historia Natural, Departamento de Simbiosis Vegetal, UNMSM. Museo de Historia Natural, Departamento de Simbiosis Vegetal. (2021)
Coastal tropical shallow lagoons are located at the Central Pacific Coast, South America. Standard cyanobacterial and microalgae collections at Puerto Viejo wetland (Grande lagoon, north of the wetland), Lima department with physical -chemical parameters were registered irregularly between 2005 –2010. Planktic natural populations of Rhabdoderma lineare Schmidle et Lauterborn from summer and fall seasons showed cell and colonial morphological variations. R.lineare bloomed in eutrophic saline conditions, associated with the unicellular rodophyte Porphyridium purpureum (Bory) Drew &Ross. They colonized habitats with temperature range of 25 - 33 ºC, salinity gradients between 13 - 20 ppt (NaCl), pH range from 8 to 9. Cyanobacterial and rodophyte phenotypic plasticity and, its distributional patterns (planktic and benthic) in the shallow lagoon are related for viable life strategy for successful colonization of coastal lagoons exposed to the annual fluctuating hydrological regime with flooding and desiccation periods. Rhabdoderma lineare y Porphyridium purpureum are new records for Peruvian flora.